Prevention strategies for adolescent depression. Issue 2 (2nd March 2014) - Bennett, Cheryl; Jones, Rhys Bevan; Smith, Daniel
Summary: Depression is missed more often in adolescents than in adults, partly because they present with symptoms different from those in adults and because many do not seek help. Early detection or the delay of onset can have a significant effect on a young person's development and social functioning. We briefly discuss diagnosis and screening instruments before presenting the wide range of educational and psychological preventive approaches developed for adolescent depression. Many of the latter are based on the cognitive-behavioural or interpersonal therapy models. We consider how clinicians might use the current evidence base to identify and prevent depression in adolescents, and outline the principles of management of the disorder. LEARNING OBJECTIVES: Identify signs and symptoms of adolescent depression and recognise the difficulties in making a diagnosis. Recognise the risk factors for adolescent depression. Appreciate the aims and theoretical concepts of prevention strategies for adolescent depression.